A holin/peptidoglycan hydrolase‐dependent protein secretion system. Issue 3 (12th October 2020) - Palmer, Tracy; Finney, Alexander J.; Saha, Chayan Kumar; Atkinson, Gemma C.; Sargent, Frank
Abstract: Gram‐negative bacteria have evolved numerous pathways to secrete proteins across their complex cell envelopes. Here, we describe a protein secretion system that uses a holin membrane protein in tandem with a cell wall‐editing enzyme to mediate the secretion of substrate proteins from the periplasm to the cell exterior. The identity of the cell wall‐editing enzymes involved was found to vary across biological systems. For instance, the chitinase secretion pathway of Serratia marcescens uses an endopeptidase to facilitate secretion, whereas the secretion of Typhoid toxin in Salmonella enterica serovar Typhi relies on a muramidase. Various families of holins are also predicted to be involved. Genomic analysis indicates that this pathway is conserved and implicated in the secretion of hydrolytic enzymes and toxins for a range of bacteria. The pairing of holins from different families with various types of peptidoglycan hydrolases suggests that this secretion pathway evolved multiple times. We suggest that the complementary bodies of evidence presented is sufficient to propose that the pathway be named the Type 10 Secretion System (TXSS). Abstract : We describe a protein secretion system in Gram‐negative bacteria that uses a holin membrane protein in tandem with a cell wall editing enzyme. The pairing of holins from different families with various types of peptidoglycan hydrolases suggests that this secretion pathway evolved multiple times. We propose that the pathway be named the Type 10 Secretion System (TXSS).